2019
DOI: 10.1111/ocr.12339
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian network meta‐analysis of orthopaedic treatment in Class III malocclusion: Maxillary protraction with skeletal anchorage or a rapid maxillary expander

Abstract: To evaluate and compare the effectiveness of orthopaedic treatment for Class III malocclusions using skeletal anchorage or a rapid maxillary expander for maxillary protraction. Electronic databases, including PubMed, EMBASE, Cochrane Library and Web of Science, were searched for randomized controlled trials (RCTs) and non‐randomized clinical trials (CCTs) for orthopaedic treatment of Class III malocclusions. Five interventions were studied: a facemask with a maxillary temporary anchorage device (MTAD), a bone‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In the present study, SAFM, BAMP, BAC3E, BARME‐FM and BARME‐ME were classified as five separate bone‐anchored maxillary protraction protocols for skeletal Class III malocclusion. Publications with identical samples were carefully excluded to avoid magnifying the effects of certain treatments, which was ignored in some previous studies 27,28 . Besides, we included four comparative studies 6,15,16,29 on bone‐anchored appliances, which were in absence in the previous NMA 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, SAFM, BAMP, BAC3E, BARME‐FM and BARME‐ME were classified as five separate bone‐anchored maxillary protraction protocols for skeletal Class III malocclusion. Publications with identical samples were carefully excluded to avoid magnifying the effects of certain treatments, which was ignored in some previous studies 27,28 . Besides, we included four comparative studies 6,15,16,29 on bone‐anchored appliances, which were in absence in the previous NMA 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes of IMPA (mean ±SD) Publications with identical samples were carefully excluded to avoid magnifying the effects of certain treatments, which was ignored in some previous studies. 27,28 Besides, we included four comparative studies 6,15,16,29 on bone-anchored appliances, which were in absence in the previous NMA. 27 Our excessive work was likely not only to provide a reference for clinicians, but also to be a reference for comparisons of multiple maxillary protraction protocols for future study.…”
Section: Changes Of U1-sn (Mean ±Sd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Maxillary protraction transmits orthopaedic force to the nasomaxillary complex via intraoral devices. In a previous study, Wu et al 4 demonstrated that maxillary protraction could effectively promote maxillary growth and correct the abnormal intermaxillary relationship. However, this technique is also associated with dental side effects, including labial inclination of the maxillary incisors and lingual inclination of the mandibular incisors 5 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to dental implants, they are usually loaded upon insertion with continuous forces of low magnitude (Luzi et al, 2009). They were shown to increase treatment efficacy for several indications, to extend the range of orthodontic treatment opportunities, and to be almost independent from patient adherence (Becker et al, 2018; Wu et al, 2020; Jia et al, 2021). Especially when placed in the anterior palate, failure rates were found to be low (Papageorgiou et al, 2012; Alharbi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%